MUTUAL RECOGNITION OF JUDICIAL DECISIONS AS BASIS FOR OBTAINING AND TRANSFER OF EVIDENCE IN CRIMINAL PROCEEDINGS - Bugarski, Tatjana; Pisarić, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
Modern forms of criminality whose hallmark is crossborder set new requirements before judicial authorities relating to the recruitment and transfer of evidence for the purposes of criminal proceedings. On the recruitment and transfer of evidence in criminal matters affecting space validity of criminal legislation, the way regulation of international legal assistance in criminal matters and guaranteed basic human rights and freedoms. Consequently, the problem of obtaining and transfer of evidence in the context of international legal assistance in criminal matters is extremely complex, relevant and important, and in this work she was given special attention. The principle of mutual assistance and mutual recognition of judicial decisions and the European Investigation Order in criminal matters are the basic issues that the authors deal in this paper work. This issue is very important today because after May 2017, the European Investigation Order in criminal matters will be the only instrument for the recruitment and transfer of evidence between countries of the European Union. Special attention was paid to the principle of mutual recognition of court decisions on which this instrument is based, as well as the issue of evaluation of evidence obtained abroad. Keywords: criminal procedure, international cooperation, mutual assistance, mutual recognition of judicial decisions, evidence, European Investigation Order in criminal matters